Analisis Sensitivitas Pada Model Matematika Penyebaran Penyakit Demam Dengue dengan Laju Insidensi NonLinier - I Putu Winada Gautama; Ni Kadek Nova Anggarani; I Made Eka Dwipayana; Putu Veri Swastika (Publisher : Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
Abstract: Dengue fever is a disease that can be fatal if not treated seriously. This disease is transmitted to humans through the Aedes Aegypti mosquito. Mathematical modeling is a tool used to understand the dynamics of dengue fever. Incomplete data creates uncertainty in the parameter values of the mathematical model. Uncertainty analysis to determine these parameters using sensitivity analysis. This study found that the bite rate of susceptible and infected mosquitoes and the mosquito death rate have a large influence on changes in the value of . Human recovery rate (r), mosquito mortality rate , and human mortality rate have a major influence on infected human individuals . The bite rate of susceptible and infected mosquitoes has the most positive influence on the number of infected mosquitoes . The mortality rate of mosquitoes had the most negative relationship with the number of mosquitoes infected with . Numerical simulations are carried out to determine the dynamics that occur when parameter values are increased or decreased. Keywords: Sensitivity Analysis, Dengue Fever, Mathematical Modeling